Uji Efek Anti-inflamasi dan Analgesik Ekstrak Etanol 70% Kulit Batang Kayu Manis (Cinnamomum burmannii Blume.) Secara In Vivo - Dewi, Rika Sari; Sandhiutami, Ni Made Dwi; Evangelia, Beatrix Melani; Bakhtiar, Muhammad Taher (Faculty of Pharmacy, Universitas Pancasila, 2023)
Cinnamon bark is known as a medicinal plant to has anti-inflammatory and analgesic effects in vitro. This activity is due to bark of cinnamon containing several compounds including cinnamaldehyde, cinnamic alcohol, cinnamic acid and coumarin. The aim of this study was to observe anti-inflammatory and analgesic effects in vivo. Anti-inflammatory test using Winter method and rats. Rats were divided into five groups negative control (aquadest), positive control (sodium diclofenac), and three extract groups with different doses (300, 400, and 500 mg/kg BW). In an analgesic test using the Siegmund method and mice. Mice were also divided into five groups negative control (aquadest), positive control (sodium diclofenac), and three extract groups with different doses (300, 400, 500 mg/kg BW). Based on a statistical test, 70% ethanol extract of cinnamon bark has anti-inflammatory and analgesic effects, also showed that there was a significant difference between the positive controls and the three extract doses. This shows that the anti-inflammatory and analgesic activity of diclofenac sodium is better than the ethanol extract of cinnamon bark in reducing the edema volume of rats and the amount of mice stretch. In conclusion,cinnamon bark showed no significant increment in high doses of anti-inflammatory and analgesic.